On the Best (α;β)-Approximations of Convex Functions by Constants in Integral Metrics - Polyakov, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We prove inequalities connecting the constants of the best (α;β) -approximation in the space L p for various values of p.